Development of the Stress of Immigration Survey: A Field Test Among Mexican Immigrant Women. Issue 1 (January 2016) - Sternberg, Rosa Maria; Nápoles, Anna Maria; Gregorich, Steven; Paul, Steven; Lee, Kathryn A.; Stewart, Anita L.
Abstract : The Stress of Immigration Survey (SOIS) is a screening tool used to assess immigration-related stress. The mixed methods approach included concept development, pretesting, field testing, and psychometric evaluation in a sample of 131 low-income women of Mexican descent. The 21-item SOIS screens for stress related to language, immigrant status, work issues, yearning for family and home country, and cultural dissonance. Mean scores ranged from 3.6 to 4.4 (a scale of 1-5, higher is more stress). Cronbach α values were more than 0.80 for all subscales. The SOIS may be a useful screening tool for detecting high levels of immigration-related stress in low-income Mexican immigrant women.